2017
DOI: 10.1103/physreve.96.012224
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing mutual synchronization of rhythmic spatiotemporal patterns in reaction-diffusion systems

Abstract: Optimization of the stability of synchronized states between a pair of symmetrically coupled reaction-diffusion systems exhibiting rhythmic spatiotemporal patterns is studied in the framework of the phase reduction theory. The optimal linear filter that maximizes the linear stability of the in-phase synchronized state is derived for the case where the two systems are nonlocally coupled. The optimal nonlinear interaction function that theoretically gives the largest linear stability of the in-phase synchronized… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The present framework can also be extended to such situations and can be used to derive the optimal coupling schemes between two coupled spatiotemporal oscillations. A study in this direction is reported in our forthcoming article [51], where improvement in the stability of synchronized states between reaction-diffusion systems by introducing linear spatial filters into mutual coupling is considered.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present framework can also be extended to such situations and can be used to derive the optimal coupling schemes between two coupled spatiotemporal oscillations. A study in this direction is reported in our forthcoming article [51], where improvement in the stability of synchronized states between reaction-diffusion systems by introducing linear spatial filters into mutual coupling is considered.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…We seek for the optimal K opt that gives the maximum stability of the synchronized state, and compare the results for K opt with those for the identity coupling, i.e., K I given by Eq. (51). The overall intensity P is fixed at P = 0.1 in the following.…”
Section: B Brusselatormentioning
confidence: 99%
“…Reaction-diffusion systems can describe a wide class of rhythmic spatiotemporal patterns observed in chemical and biological systems, such as circulating pulses on a ring, oscillating spots, target waves, and rotating spirals. Synchronization dynamics of reaction-diffusion systems has been studied in [21,22] using phase reduction theory. It has been shown that reaction-diffusion systems can exhibit synchronization in a similar way to low-dimensional oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated a phase reduction method for limit-cycle solutions to the following partial differential equations: (i) nonlinear Fokker-Planck equations representing collective oscillations of globally coupled noisy dynamical elements [20,21], (ii) fluid equations representing oscillatory thermal convection in ordinary Hele-Shaw cells [22,23], (iii) reaction-diffusion equations representing spatiotemporal rhythms in chemical and biological systems [24,25], and (iv) fourth-order nonlinear partial differential equations representing beating flagella [26]; more precisely, the first and second equations are partial differential integral equations. This method can be considered as a generalization of the conventional phase reduction method for ordinary differential equations.…”
Section: Introductionmentioning
confidence: 99%